2019
DOI: 10.1017/s2045796019000350
|View full text |Cite
|
Sign up to set email alerts
|

Reducing coercion in mental healthcare

Abstract: AimsTo examine the extent and nature of coercive practices in mental healthcare and to consider the ethical, human rights challenges facing the current clinical practices in this area. We consider the epidemiology of coercion in mental health and appraise the efficacy of attempts to reduce coercion and make specific recommendations for making mental healthcare less coercive and more consensual.MethodsWe identified references through searches of MEDLINE, EMBASE, PsycINFO and CINAHL Plus. Search was limited to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 64 publications
1
71
0
10
Order By: Relevance
“…9 This is compounded by the fact that agitated patients may often experience coercion, defined as actions performed on a patient that cause loss of self-determination, ranging from involuntary detention or seclusion to use of forcible treatment with restraints. 10 A recent observational study 11 found that 61% of agitated patients felt coerced by police or prehospital staff before ED arrival. Experiences of coercion may limit the ability of ED clinical staff to engage in a dialogue and create a therapeutic bond.…”
Section: Introductionmentioning
confidence: 99%
“…9 This is compounded by the fact that agitated patients may often experience coercion, defined as actions performed on a patient that cause loss of self-determination, ranging from involuntary detention or seclusion to use of forcible treatment with restraints. 10 A recent observational study 11 found that 61% of agitated patients felt coerced by police or prehospital staff before ED arrival. Experiences of coercion may limit the ability of ED clinical staff to engage in a dialogue and create a therapeutic bond.…”
Section: Introductionmentioning
confidence: 99%
“…Involuntary admission of adults to psychiatric hospitals has obvious implications for people's autonomy and liberty, is ethically and professionally controversial and expensive for services and the wider society [1]. The use of involuntary admissions can also be traumatic for both the person in question and their relatives [1].…”
Section: Introductionmentioning
confidence: 99%
“…Committee As there is little research on coercion in mental health care [30] and supporting data about how to make mental health care more consensual, the present survey was undertaken.…”
Section: Introductionmentioning
confidence: 99%